Listopadowe dni 1918 roku w Bydgoszczy w relacji burmistrza miasta Hugona Wolffa (Kronika Bydgoska, 2020)
This article features memories of the last Prussian Mayor of the City of Bydgoszcz, Hugo Wolff, of November and December 1918. He describes events that took place in Bydgoszcz during the first weeks after the defeat of Germany and the end of World War I. This manuscript, stored in the District Museum in Bydgoszcz, has not been published so far. It provides a lot of new information and facts from the first postwar months in the city, reported and commented upon by the highest ranking officer in the city.